WAQF PARTICIPATION AND AWARENESS: AN EXPLORATORY STUDY IN THE WEST COAST OF SABAH, MALAYSIA - Nur Shahida Ab Fatah, Noorhayati Mansor, Noraizan Ripain, Wan Anisah Endut (International Journal of Research Science and Management, 2017)
Unlike Malaysian society in the Peninsular where Islamic values and lifestyles predominate, ethnic groups in Sabah are currently not exposed to waqf as an Islamic economic system. The geographical and cultural factors may contribute to the lack of awareness in waqf activities. Accordingly, this exploratory research examines the current level of waqf participation among Muslims in Sabah focusing on knowledge, procedural requirements and awareness of waqf. Three major districts on the West Coast of Sabah which are Kota Kinabalu, Tuaran and Penampang were chosen from the total 36 districts. The West Coast covers about 10% of the total area of the State and is home to 30% of Sabah’s total population. A total of 87 individuals participated in the survey. Results of the study suggest that only awareness and procedural requirements contribute significantly (p=0.000) to the level of waqf participation in these areas and indicates that knowledge does not significantly affect waqf participation. Thus, having knowledge of waqf alone is insufficient to motivate waqf of individual assets. Rather, understanding of the procedures and requirements plays the major role. This research suggests awareness programs to educate the society to improve the public’s participation in waqf activities.